An induction period in the formation of the dissipative structures in solutions of anthraquinone - Karitskaya, S. G.; Ponomarev, S. (INST ADVANCED SCIENCE EXTENSION, PO BOX 23-31, TAIPEI, TAIWAN, 2017)
The purpose of the present work is to characterize the induction period in the kinetics of the formation of luminescent dissipative spatial temporal structures in solutions of anthraquinone. Such structures are formed under ultraviolet illumination in isopropyl alcohol solutions and silicone polymeric films. The structures exhibit three distinctive stages in time, induction, “fast”, and “slow”. During the induction period, no luminescence is observed, and the “fast” and “slow” stages are characterized by the appearance of bright luminescent products. Although similar luminescent structures have been previously reported in literature, no study has been conducted on the characterization of their induction periods. In our work, the observed luminescence is attributed to ketyl radicals while the formation of the structures requires heat and mass (oxygen and solvent radicals) transfer to and from the reaction zones. The induction period appears to be highly sensitive to the intensity of illumination, oxygen and solvent radicals concentrations.
Keywords: Luminescence; Anthraquione; Ketyl; Induction period; Oxygen